2021
DOI: 10.1038/s41598-021-99222-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on the association between alcohol consumption and the development of chronic kidney disease

Abstract: The influence of body mass or metabolic capacity on the association between alcohol consumption and lower risks of developing chronic kidney disease (CKD) is not fully elucidated. We examined whether the body mass index (BMI) affects the association between drinking alcohol and CKD. We defined CKD as an estimated glomerular filtration rate decline < 60 mL/min/1.73 m2 and/or positive proteinuria (≥ 1+). Participants were 11,175 Japanese individuals aged 40–74 years without baseline CKD who underwent annual h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The search strategy identified 1457 articles, 1423 of which were excluded after review of the title or abstract ( Figure S1 ). Of the 34 publications selected, the present meta-analysis finally included 12 publications [ 19 , 20 , 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] from 11 cohort studies ( N = 14,634,940), including the Physicians’ Health Study (PHS) study which defined the outcome as eGFR of <55 mL/min [ 32 ]. We excluded 23 publications because two publications were cross-sectional studies [ 41 , 42 ], two did not assess alcohol consumption (g/day) as a predictor of proteinuria and/or low GFR [ 43 , 44 ], three categorized alcohol consumption into only two levels (none vs. ≥1 drink/day [ 45 ], no use vs. use of alcohol [ 46 ], and alcohol consumption of <20 vs. ≥20 g/day [ 47 ]), four did not stratify current drinkers by alcohol consumption level (g/day) [ 48 , 49 , 50 , 51 ], one had the highest alcohol consumption category with the lower boundary of <12 g/day, [ 52 ] one had a sex-specific definition of alcohol consumption level [ 53 ], one did not define the outcome of CKD [ 54 ], seven did not have the outcome of incidence of proteinuria or low GFR [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ], one had missing information on the number of participants of alcohol consumption categories [ 62 ], and one reported similar results in previous publications [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The search strategy identified 1457 articles, 1423 of which were excluded after review of the title or abstract ( Figure S1 ). Of the 34 publications selected, the present meta-analysis finally included 12 publications [ 19 , 20 , 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] from 11 cohort studies ( N = 14,634,940), including the Physicians’ Health Study (PHS) study which defined the outcome as eGFR of <55 mL/min [ 32 ]. We excluded 23 publications because two publications were cross-sectional studies [ 41 , 42 ], two did not assess alcohol consumption (g/day) as a predictor of proteinuria and/or low GFR [ 43 , 44 ], three categorized alcohol consumption into only two levels (none vs. ≥1 drink/day [ 45 ], no use vs. use of alcohol [ 46 ], and alcohol consumption of <20 vs. ≥20 g/day [ 47 ]), four did not stratify current drinkers by alcohol consumption level (g/day) [ 48 , 49 , 50 , 51 ], one had the highest alcohol consumption category with the lower boundary of <12 g/day, [ 52 ] one had a sex-specific definition of alcohol consumption level [ 53 ], one did not define the outcome of CKD [ 54 ], seven did not have the outcome of incidence of proteinuria or low GFR [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ], one had missing information on the number of participants of alcohol consumption categories [ 62 ], and one reported similar results in previous publications [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…An association between alcohol consumption and incidence of proteinuria stratified by alcohol consumption of 0.1–12.0, 12.1–36.0, 36.1–60.0, and >60.0 g/day is shown in Figure 1 . The pooled result of 7 studies [ 19 , 20 , 21 , 35 , 37 , 38 , 40 ] that included 14,503,097 participants showed that drinkers were at a significantly lower risk of incidence of proteinuria than non-drinkers (overall RR 0.95 [95% confidence interval 0.93, 0.98]). However, the association was highly dependent on the alcohol consumption levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measures of dialysis adequacy, such as serum creatinine, blood urea, serum potassium, phosphorous, and quality of life, all improve signi cantly after a prescribed intradialytic exercise regimen (Paluchamy & Vaidyanathan, 2018). Increased alcohol intake and cigarette smoking are known risk factors for the onset and CKD progression (Hashimoto et al, 2021) (Yacoub et al, 2010). A study reported that mild-spectrum CKD individuals showed increased saturated fat, salt, and protein intake.…”
Section: Introductionmentioning
confidence: 99%